2015
DOI: 10.1007/s00240-015-0786-0
|View full text |Cite
|
Sign up to set email alerts
|

Flexible ureteroscopic laser lithotripsy for upper urinary tract stone disease in patients with spinal cord injury

Abstract: The objective of this study is to present the outcomes of flexible ureteroscopic laser lithotripsy (URS) for upper urinary tract stone disease in spinal cord injury (SCI) patients performed by a single surgeon. A retrospective analysis was performed for SCI patients treated with flexible URS for proximal ureter and kidney stone disease by a single surgeon between 2003 and 2013. Patient characteristics, operative outcomes, metabolic evaluation, and stone analyses were assessed in detail. A total of 27 URS proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Ho:YAG laser lithotripsy is an efficient and safe technology for the treatment of urinary stones in almost any patient group, ranging from young children to adults and older patients, pregnant women to spinal cord injury patients, from solitary to allograft kidneys, or patients on certain medications and anticoagulants. Its safety profile has been largely demonstrated and still is in countless and recent safety-oriented studies [ 87 •, 88 •, 89 , 90 •, 91 98 , 99 •, 100 , 101 •]. Yet there are still some direct and indirect complications and safety concerns about laser lithotripsy, which have been recently researched.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Ho:YAG laser lithotripsy is an efficient and safe technology for the treatment of urinary stones in almost any patient group, ranging from young children to adults and older patients, pregnant women to spinal cord injury patients, from solitary to allograft kidneys, or patients on certain medications and anticoagulants. Its safety profile has been largely demonstrated and still is in countless and recent safety-oriented studies [ 87 •, 88 •, 89 , 90 •, 91 98 , 99 •, 100 , 101 •]. Yet there are still some direct and indirect complications and safety concerns about laser lithotripsy, which have been recently researched.…”
Section: Bibliographic Search Resultsmentioning
confidence: 99%
“…Currently, FURS is most commonly used in the treatment of patients with proximal ureteral and renal calculi (20). A previous study indicated that ureteroscopic laser lithotripsy can be used as an effective treatment modality for patients with spinal cord injury and with upper urinary tract calculi (21). Additionally, MUS can be used in the treatment of malignant ureteral obstruction (22).…”
Section: Discussionmentioning
confidence: 99%
“…FURS is specifically indicated for professionals including airline and air force pilots, young women who do not wish to manifest surgical scars, and even pregnant women. [710162930] Traditional PCNL in the prone position has a higher surgical risk for some patients, such as those with severe kyphosis, cardiopulmonary dysfunction, obesity, or spinal cord injury. The oblique supine lithotomy position, on the other hand, is more comfortable and better tolerated by patients and is a familiar position for surgical staff, thus minimizing anesthetic and operative risks.…”
Section: Discussionmentioning
confidence: 99%
“…The oblique supine lithotomy position, on the other hand, is more comfortable and better tolerated by patients and is a familiar position for surgical staff, thus minimizing anesthetic and operative risks. [7810202130] Therefore, the beneficial implications for FURS treatment for calyceal diverticular stone in the oblique supine lithotomy position are broader than for PCNL. In the present study, two asymptomatic patients included a pilot and an astronaut with diverticular stones found during the physical examination.…”
Section: Discussionmentioning
confidence: 99%